A De Novo Designed Metalloenzyme for the Hydration of CO21. (18th June 2014) - Cangelosi, Virginia M.; Deb, Aniruddha; Penner‐Hahn, James E.; Pecoraro, Vincent L.
Abstract Protein design will ultimately allow for the creation of artificial enzymes with novel functions and unprecedented stability. To test our current mastery of nature's approach to catalysis, a ZnII metalloenzyme was prepared using de novo design. α3DH3 folds into a stable single‐stranded three‐helix bundle and binds ZnII with high affinity using His3O coordination. The resulting metalloenzyme catalyzes the hydration of CO2 better than any small molecule model of carbonic anhydrase and with an efficiency within 1400‐fold of the fastest carbonic anhydrase isoform, CAII, and 11‐fold of CAIII.